ANALISIS KINERJA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KABUPATEN KUTAI BARAT - Muyo, Maya Chressensia (EKONOMIA, 2017)
In achieving excellent service, performance measurement methods are needed to assess the company's performance accurately and thoroughly. In this case the method to be used is the Balanced Scorecard. Objective measurements of the Balanced Scorecard method is to measure the performance of the company from four perspectives, namely financial perspective, customer perspective, internal business processes, and learning and growth perspective. Author measurement of performance on BPKAD Kutai Barat using data at the time before becoming BPKAD West Kutai and after becoming BPKAD Kutai Barat to analyze the financial perspective, customer perspective, internal business processes, and learning and growth perspective.From the research that has been made known that the performance BPKAD Kutai Barat district as a whole is quite good, it is shown by the value Scorecard produced from each perspective. The conclusion that can be drawn through the analysis that has been done that the Balanced Scorecard is the best method to evaluate the performance of the company, because the Balanced Scorecard raised important aspects are overlooked by the performance of traditional ways, such as aspects of human resources, the system used in the company, operational processes, and aspects of customer satisfaction, so that the measurement results with the Balanced Scorecard will be more accurate. Accurate performance measurement results are very important for management, both at the planning, decision-making and control, as well as in realizing the vision and mission of the company.